Phenethyl p-coumarate and N-phenethyl-p-coumaramide : synthesis, characterization, docking studies and anticancer activity through P388 cell - Firdaus,; Soekamto, Nunuk Hariani; Seniwati,; Firdausiah, Syadza; Rasyid, Herlina; Bahja,; Islam, Muhammad Fajar (Penerbit Universiti Kebangsaan Malaysia, 2022)
Most p-coumaric acid derivatives and molecules containing phenethyl moiety have a potential in anticancer activity. Thus, combining a p-coumaroyl group and a phenethyl moiety in one compound will increase anticancer activity. The principal objective of this research was to incorporate p-coumaroyl and phenethyl moieties to form an ester, phenethyl p-coumarate (5), and an amide, N-phenethyl-p-coumaramide (6), then tested their anticancer activity using P388 leukemia murine cells. The characterization by FTIR method, compound 5 gave a strong absorption band of alkyl C-O bond that appears at 1165,00 cm-1, and compound 6 gave a sharp and medium absorption band of N-H bond that appears at 3396.64 cm-1. Docking studies of both compounds showed a hydrogen bond with Ile839 residue, and an additional hydrogen bond appeared between compound 6 and Ser991 residue. Based on their activity against P388 leukemia murine cells, these compounds are more active than their analog compounds of N-feruloylpiperidine and N-feruloylmorpholine, which have been synthesized previously. Compounds 5 and 6 have a high potential to be used as anticancer drugs.